Adherence to a Paleolithic Diet in Combination With Lifestyle Factors Reduces the Risk for the Presence of Non-Alcoholic Fatty Liver Disease: A Case-Control Study - Sohouli, Mohammad Hassan; Fatahi, Somaye; Izze da Silva Magalhães, Elma; Rodrigues de Oliveira, Bianca; Rohani, Pejman; Ezoddin, Neda; Roshan, Mehdi Mehdinezhad; Hekmatdoost, Azita (Frontiers in Nutrition, 2022)
Background: Evidence suggests the role of changing traditional lifestyle patterns such as Paleolithic to modern lifestyle in the incidence and epidemic of chronic diseases. The purpose of this study was to investigate the associations between the Palaeolithic diet (PD) and the Palaeolithic-like lifestyle and the risk of NAFLD among an adult population. Materials and Methods: This case-control study was carried out among 206 patients with NAFLD and 306 healthy subjects aged >18 years. PD score was evaluated using a validated 168-item quantitative food frequency questionnaire. Also, to calculate the Paleolithic-like lifestyle score the components of physical activity, body mass index (BMI), and smoking status of the participants were combined with the score of the Paleolithic diet. Results: The mean PD and Paleolithic‑like lifestyle scores were 38.11 ± 5.63 and 48.92 ± 6.45, respectively. After adjustment for potential confounders, higher scores of adherence to the PD diet conferred a protection for the presence of NAFLD (odds ratio [OR]: 0.53; 95% confidence interval [CI]: 0.28 – 0.98; P for trend = 0.021). Furthermore, PD and healthy lifestyle habits were negatively associated with NAFLD (OR = 0.42, 95% CI 0.23 – 0.78; p for trend = 0.007). Conclusions: Our data suggests that Paleolithic diet alone and in combination with lifestyle factors were associated with decreased risk of NAFLD in a significant manner in the overall population. However, prospective studies are needed to further investigate this association.